Enhanced Colorimetric Detection of Volatile Organic Compounds Using a Dye-Incorporated Photonic Crystal-Based Sensor Array - Nah, So Hee (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.